Multilingual Assessment – Finding the Nexus? (Peter Lang International Academic Publishers, 2024)
A persistent monolingual paradigm still pervades teaching and assessment practices in different educational contexts. How is this paradigm being responded to across regions and (sub)disciplines of language study? In answering this question, the volume draws on insights from the project MULTILA – Multilingual and multimodal assessment, jointly coordinated by the University of Education, Heidelberg, Germany, and the University of the Western Cape, South Africa. This volume is an opportunity to understand practices in both environments and to identify commonalities and differences. While European contributors to the dialogue come from a language education and assessment background, their South African interlocutors approach the subject from a largely applied linguistics perspective. The outcome is an account in ten chapters of multilingual assessment from perspectives that are both disciplinary and regional.